2009
DOI: 10.1590/s0103-166x2009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização clínica e psicossocial da clientela de um ambulatório de esterilidade

Abstract: Este estudo teve como objetivo descrever características demográficas, clínicas e psicossociais da clientela de um ambulatório de esterilidade e identificar motivação para atendimento psicológico. Tratou-se de estudo retrospectivo, com 50 casais, entrevistados no início do processo de investigação médica. Constatou-se que 80% dos casais estavam na primeira união conjugal, 64% tinham até oito anos de casados, 72% não tinham filhos e 78% vinham tentando engravidar há no máximo seis anos. Desconheciam as causas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
3
0
13
Order By: Relevance
“…21 Motivation, fears and level of information about AR are some of the variables to be considered when psychological intervention is offered to couples during infertility treatment. 22 Currently, it is observed that the use of the internet can be an alternative to help with information and social support, and has a significant lower cost. Preliminary results of a study suggest that general stress may be significantly reduced in infertile women using an online cognitive behavioral approach.…”
mentioning
confidence: 99%
“…21 Motivation, fears and level of information about AR are some of the variables to be considered when psychological intervention is offered to couples during infertility treatment. 22 Currently, it is observed that the use of the internet can be an alternative to help with information and social support, and has a significant lower cost. Preliminary results of a study suggest that general stress may be significantly reduced in infertile women using an online cognitive behavioral approach.…”
mentioning
confidence: 99%
“…A infertilidade é compreendida como uma doença do sistema reprodutivo, caracterizada pela falha de se obter gravidez clínica após 12 meses ou mais de coito regular desprotegido (Corrêa, Vizzotto & Cury, 2007;Gorayeb, Borsari, Gomes, Romão & Shuhama, 2009;Van der Poel, 2012). Esta possui causas multideterminadas, como por exemplo: fatores masculinos e femininos; aumento da idade na decisão da maternidade e postergação da concepção; doenças sexualmente transmissíveis e inflamatórias do aparelho reprodutor masculino e feminino; hábitos de vida associados à sedentaridade, obesidade, tabagismo; e consumo excessivo de álcool ou de drogas ilícitas (Moura, Souza & Scheffer, 2009).…”
Section: Introductionunclassified
“…Tendo em vista o lugar hegemônico conferido à prole (Borsa & Nunes, 2011;Carter & McGoldrik, 1995;Monteiro & Teixeira, 2011), a constatação da impossibilidade de tê-los costuma acarretar um processo de grande sofrimento às famílias. Nas últimas 3 décadas, por exemplo, um número crescente de pesquisas têm evidenciado o impacto que a falta involuntária de filhos pode causar (Farinati, 1996;Gorayeb et al, 2009;Silva & Lopes, 2011).…”
Section: Introductionunclassified
See 2 more Smart Citations